Market analysis of veterinary medicines for dogs - Anastasiia G. Kolycheva; Andrey A. Rudenko; Marina I. Shopinskaya (RUDN Journal of Agronomy and Animal Industries)
Medicinal products intended for dogs were studied. According to the statistics of the AllRussian Public Opinion Research Center1, every third family in Russia has a dog. In this regard, maintaining the health of dogs is of great importance both from a psychological and social perspective. The current state of the Russian veterinary market is characterized by a reduction in the number of foreign suppliers. For example, in 2017, there were 867 veterinary drugs of foreign origin in Russia, of which approximately 180 items remained in market, but this number tend to decrease. The shares of foreign and Russian drugs presented in the Russian market are approximately equal, which indicates a great dependence on foreign suppliers. At the same time, many veterinarians prefer to use foreign drugs as the most effective and safe. However, Russian drugs recently appear in the Russian market are corresponding in quality to foreign analogues. Nowadays, they should form the basis for import substitution. The priority for import substitution should be drugs for the treatment of the most common and deadly diseases of dogs, the list of which is established by the national standard of the Russian Federation (GOST R 70040-2022) 2. According to the list, 35 of the most common diseases in practice were identifi for 10 organs and systems of dogs. The method of grading the medicinal products quality previously developed by the authors was used to select medicinal products by a treatment way. As a result, 353 drugs were selected, including 178 foreign and 175 Russian products. It was established that the supply of foreign drugs by the origin of medicines comprises 34 foreign countries, including 8 friendly and 26 unfriendly. At the same time, 148 drugs are supplied from unfriendly countries, and only 30 from friendly ones. The current trend of reducing supplies from unfriendly countries poses a threat of a shortage of medicines to Russia.